The Leaders in Informatics, Quality, and Systems (LInQS) Fellowship - Hallman, Heather; Pell, Jonathan; Ho, P. Michael; Montague, Brian; Schilling, Lisa; Sieja, Amber; Ream, Karen; Anstett, Tyler (Applied Clinical Informatics, 2024)
Background Leaders in Informatics, Quality, and Systems (LInQS) is a non-ACGME (Accreditation Council for Graduate Medical Education)-accredited 2-year training program developed to enhance training in the fields of health care delivery, quality improvement (QI), clinical informatics, and leadership.Methods This single-institution 2-year longitudinal training program grounded in QI and informed by leadership and clinical informatics includes didactics, coaching, and mentorship, all centered around individualized QI projects. The program has been available to sub-specialty fellows, advanced practice providers, and physicians.Results From 2019 to 2023, 32 fellows have been accepted into the program with 13 graduates and 16 currently enrolled. Fellows have been predominately female, physicians, and from multiple specialties but predominantly hospital medicine. Fellows' evaluations of the fellowship are highly positive, rating the didactics and mentorship aspects of the curriculum most favorably. Most fellows' projects utilized informatics solutions including clinical decision support tools to increase quality of care, improve patient outcomes, and reduce costs of care resulting in manuscript publications, national presentations, and a national specialty society award. Since matriculation, 50% of fellows received certification as Epic Physician Builders and 34% received leadership positions in clinical informatics, quality, and education.Conclusion Our experience supports the need to provide health care providers more expansive training in the areas of QI, clinical informatics, and leadership for improving health care delivery. Additional in-depth knowledge and experience in these fields may produce and benefit leaders in these fields.
Keywords: clinical informatics; quality improvement; education; leadership